2018
DOI: 10.1002/hbm.24309
|View full text |Cite
|
Sign up to set email alerts
|

Evoked directional network characteristics of epileptogenic tissue derived from single pulse electrical stimulation

Abstract: We investigated effective networks constructed from single pulse electrical stimulation (SPES) in epilepsy patients who underwent intracranial electrocorticography. Using graph analysis, we compared network characteristics of tissue within and outside the epileptogenic area. In 21 patients with subdural electrode grids (1 cm interelectrode distance), we constructed a binary, directional network derived from SPES early responses (<100 ms). We calculated in‐degree, out‐degree, betweenness centrality, the percent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 32 publications
2
35
0
2
Order By: Relevance
“…Next, based on connectivity analysis of ER networks (Hebbink et al, 2019;van Blooijs et al, 2018), we concluded that DRs are indirect responses to the stimulation. Model simulations show that they may arise from feedforward propagation of ER activity and notably projections to inhibitory populations that normally restrain neural activity.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Next, based on connectivity analysis of ER networks (Hebbink et al, 2019;van Blooijs et al, 2018), we concluded that DRs are indirect responses to the stimulation. Model simulations show that they may arise from feedforward propagation of ER activity and notably projections to inhibitory populations that normally restrain neural activity.…”
Section: Discussionmentioning
confidence: 94%
“…We use the detected ERs to construct a network representing effective connectivity (Entz et al., ; Hebbink et al., ; Keller et al., ; van Blooijs et al., ). Each electrode represents a node in this network.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…SPES networks might be a good alternative as such models would incorporate more physiological connections. Moreover, SPES ER networks contain information about both the seizure onset zone [37,38] and seizure propagation [35,36]. It would therefore be interesting to compare SPES and ictal networks.…”
Section: Overviewmentioning
confidence: 99%